A Free-Standing Pt-Nanowire Membrane as a Highly Stable Electrocatalyst for the Oxygen Reduction Reaction - Liang, Hai-Wei; Cao, Xiang; Zhou, Fei; Cui, Chun-Hua; Zhang, Wen-Jun; Yu, Shu-Hong (Advanced materials (Weinheim), 2011)
A free‐standing Pt‐nanowire membrane fabricated via a multistep templating process is used as an electrocatalyst for the oxygen reduction reaction (ORR). It exhibits remarkably high stability and good catalytic activity due to its unique nanowire‐network structure.